2022
DOI: 10.3126/janr.v5i1.50834
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization and diversity of Nepalese garlic (Allium sativum L.) landraces

Abstract: A total 37 garlic landraces collection from Nepal Genebank were characterized using phenotypic trait maps or agro morphological markers at National Agriculture Genetic Resources Centre (Genebank), Khumaltar, Lalitpur, Nepal during 2017 using quantitative and qualitative traits. Shannon and Weaver diversity index (H’) analysis revealed significant intra landrace diversity for both quantitative and qualitative traits. Nine principal components contributed 100 % to the cumulative variance and the first three prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…While Mehta AA et al (2015) 8 and Patil A et al (2017) 13 conducted similar studies on the Maharashtrian population of westernIndia. In another study conducted by Butt MK et al (2017) 24 , which included students from Lahore, Pakistan while Karki RK et al (2014) 6 and Shreshtha R et al (2014) 9 conducted their studies on the population of Nepal region. In another studies conducted by Eboh D et al (2013) 25 and Ekanem AU et al (2014) 16 were conducted on population of Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While Mehta AA et al (2015) 8 and Patil A et al (2017) 13 conducted similar studies on the Maharashtrian population of westernIndia. In another study conducted by Butt MK et al (2017) 24 , which included students from Lahore, Pakistan while Karki RK et al (2014) 6 and Shreshtha R et al (2014) 9 conducted their studies on the population of Nepal region. In another studies conducted by Eboh D et al (2013) 25 and Ekanem AU et al (2014) 16 were conducted on population of Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the present study were similar to the studies conducted by Shukla S et al (2016) 17 , Mohsin TS et al (2019) 26 , and Salmani D et al (2016) 22 , the most predominant fingerprint pattern observed was loop patternin majority of cases followed bywhorls and arch pattern. A study by Shrestha DB et al (2016) 9 , it was found that the loop pattern was the most predominant pattern with 48.47% cases, followed by whorls with 32.71% cases, arch pattern was observed in 15.93% cases and composite pattern in 2.88% cases. Another study conducted by Shrestha et al (2014) 14 ,also observed the similar patterns where looppattern was the most predominant pattern observed in 52.7% cases, followed by whorls with 41.3% cases, arch pattern in 5.05% cases and composite pattern in 0.85% cases.…”
Section: Patterns Of Fingerprints Among the Femalesmentioning
confidence: 93%
See 1 more Smart Citation
“…Width of leaves were maximum (2.24 cm) in genotype ARM 01 followed by ARM 04 (2.05 cm), Kathmandu Local (1.06 cm), Chinese (1.05 cm) and Malikabota (1.05 cm) whereas the narrowest leaves (0.87 cm) were recorded from ARM 02 and Holeri followed by Mugu Local (0.90 cm), ARM 03 (0.92 cm) and ARM 05 (0.92 cm) (Table 2). Researchers reported [16,20] significant variation in width of leaves was due to the difference between genotypes.…”
Section: Width Of Leafmentioning
confidence: 99%
“…The most used classification is based on the morphological description of cultivars (Engeland, R.L., 1991). However, garlic is able to adapt to its environment, resulting in wide ranges of morphological characteristics within a cultivar (Mossie et al, 2021;Shrestha et al, 2022). Another result is duplicate names for a genetically identical cultivar and a single name for cultivars with different characteristics.…”
Section: Introductionmentioning
confidence: 99%